1978
DOI: 10.1136/ard.37.4.333
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between uric acid and potassium in normal subjects.

Abstract: SUMMARYThe serum uric acid concentration in normal healthy subjects has been studied in relation to sex, height, weight, lean body mass measured from total body potassium and predicted from the Hume-Weyers formula (1971), total body potassium, plasma potassium and urea, and packed cell volume. The strongest correlation was found with sex, but height, weight, total body potassium, lean body mass (measured and predicted) also correlated significantly with serum uric acid concentration. However, when the sex vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Indirect evidence can be found in an earlier study in normal volunteers, 40 in which the total plasma uric acid pool was found to correlate positively with total body potassium. The conclusion was that both total body potassium and urate pool were reflections of lean body mass.…”
mentioning
confidence: 88%
“…Indirect evidence can be found in an earlier study in normal volunteers, 40 in which the total plasma uric acid pool was found to correlate positively with total body potassium. The conclusion was that both total body potassium and urate pool were reflections of lean body mass.…”
mentioning
confidence: 88%